TI_GERICHTE 80.2023.132 vom 1. Juni 2023 , Deduzioni: liberalità, pubblica utilità, non quota associativa versata a sindacato - TI Tribunale d'appello (2023)
Deduzioni: liberalità, pubblica utilità, non quota associativa versata a sindacato